Evaluation of touch preparation cytology during frozen-section diagnoses of pulmonary lesions. Issue 8 (30th June 2010) - Rakha, E A; Haider, A; Patil, S; Fourtan, H; Chaudry, Z; Soomro, I N
Abstract : Background: Intraoperative frozen section (FS) examination in thoracic surgery is a reliable method for diagnosis and staging of pulmonary lesions and provides a valuable guide in directing the extent of the ongoing surgical procedure. However, the contribution of touch preparation cytology (TPC) to FS diagnosis remains unclear. Aim: To assess the utility of routinely performed TPC during FS diagnoses of pulmonary lesions. Methods: In this study FS and TPC for all patients who had undergone FS diagnoses of pulmonary lesions in a 6-year period were reviewed by two pathologists. Results: A total of 155 consecutive patients underwent intraoperative FS procedure, and 110 of those cases had TPC available for review. TPC was diagnostic or contributory to FS diagnosis in 97 (88%) cases, and non-contributory in 13 cases, mainly due to low or inadequate cellularity. TPC provided useful information regarding tumour subtyping, but it was less sensitive in the diagnosis of mucinous neoplasms and was less specific in the assessment of bronchial resection margins. In granulomatous lesions with or without necrosis, TPC was diagnostic in 10 (91%) cases. In five cases (including four cases of tuberculosis), TPC was the only diagnostic tool since FS was not completed. In conclusion, TPC showed high sensitivity and specificity rates and was contributory to FS diagnosis of pulmonary lesions. TPC provides a fast, less-expensive method of diagnosis, utilises a minimal amount of tissue, and can save processing of fresh frozen tissues in certain situations such as tuberculous lesions.